Factors Related To The Incidence Of Hypertension In 20-44 Years Of Age In The Work Area Uptd Community Health Center Sp-1 Kalibumi, Nabire Regency - Norinda Jikwa; Nur Susan Iriyanti Ibrahim; Alfred D Lambey (Asosiasi Riset Ilmu Kesehatan Indonesia, 2025)
Hypertension is one of the most common cardiovascular diseases and is suffered by many people. Based on Southeast Asian data, hypertension causes around 8 million deaths each year, with cases in Southeast Asia around 1.5 million deaths due to hypertension. Data from the Work Area of the SP 1 Kalibumi Health Center UPTD, the incidence of hypertension in 2023 was 116 people aged 20-24 years. Objective: to determine the factors associated with the incidence of hypertension at the age of 20-44 years in the Work Area of the SP-1 Kalibumi Health Center UPTD, Nabire Regency. Method: This type of research is quantitative using a cross-sectional study approach, conducted in the work area of the SP-1 Kalibumi Health Center UPTD, Nabire Regency. A sample of 54 respondents aged 20-44 years who met the inclusion and exclusion criteria. Data processing was carried out using SPSS version 16. Results: The results of the Chi-Square statistical test obtained a p-value = 0.00 for the diet variable, p-value = 0.07 for the physical activity variable, p-value = 0.34 for the smoking habit variable, and p-value = 0.06 for the family history variable. Conclusion: The variables related to the incidence of hypertension are diet, while physical activity, smoking habits, and family history have no relationship. Suggestion: The community can regulate and maintain their diet to avoid hypertension. For further research, observe other variables for the incidence of hypertension.